Implementación del lenguaje XBRL en las Pymes de Colombia (2021)
The importance of this research lies in the manifest difficulty on the part of Colombian entrepreneurs, in their process of convergence in the implementation of international accounting models, a situation accentuated by the constant changes in the economy.